Modern Experience of Pharmacotherapeutic Use and Effectiveness of Endolumbal Administration of Glucocorticoids in Progressive Types of Course for Multiple Sclerosis - Vasylovskyy, Vitaliy; Nehreba, Tetiana; Chernenko, Maksym; Voloshyna, Nataliya; Pohulaieva, Tetiana; Voloshyn-Haponov, Ivan (SSP Modern Pharmacy and Medicine, 2024)
Effective pharmacotherapy of low-bondly progredient forms of the multiple sclerosis is a difficult task that requires the search for new and improving existing methods of treatment. The author set the task to the optimize the treatment of progredient forms of multiple sclerosis using the method of endolumbal introduction of glucocorticoids and to evaluate its efficiency. The results of treatment of 76 patients with poor curable progresses of multiple sclerosis by intratracal introduction of glucocorticoids (dexamethasone) are presented in the study. The advantages of method, methodic of introduction, the patient`s selection parameters were given. The efficiency criterions of intration of glucocorticoids were defined, including the neurological deficiency regress, stabilization and the delay of multiple sclerosis progressing. Integral assessment of efficiency was made as 4 gradations: “good rate”, “low” and “absence of effect”. The positive dynamics of neurological state was registered predominantly on spastic-paretic syndrome with presence of several active foci with contrast enhancement. The sphincter infringements and brain stem symptomatic were observed as rarely reversible, extremely rarely - cerebellar symptom complex. As the results of the treatment (the term of the observation – 6 months and more) 80.2% of multiple sclerosis patrols marked the efficiency as "good" and "moderate". The obtained data indicated the reasonability of the proposed method of treatment for patrols with saversive counses of multiple sclerosis, occurring inly with spinal symptomatic.